CdS Nanowires Decorated with Ultrathin MoS2 Nanosheets as an Efficient Photocatalyst for Hydrogen Evolution. Issue 6 (16th February 2016) - He, Jie; Chen, Lang; Wang, Fu; Liu, Ying; Chen, Peng; Au, Chak‐Tong; Yin, Shuang‐Feng
Abstract: CdS nanowires decorated with ultrathin MoS2 nanosheets were synthesized for the first time by ultrasonic exfoliation by using dimethylformamide as the dispersing agent. An excellent hydrogen evolution rate of 1914 μmol h −1 (20 mg catalyst) under visible‐light irradiation ( λ ≥400 nm, ≈154 mW cm −1 ) and an apparent quantum yield of 46.9 % at λ =420 nm were achieved over the MoS2 /CdS composite. The presence of ultrathin MoS2 nanosheets (rich in active edge sites) on the CdS surface promotes the separation of photogenerated charge carriers and facilitates the surface processes of photocatalytic hydrogen evolution. Abstract : Down to the wire : A composite comprising CdS nanowires decorated with ultrathin MoS2 nanosheets is synthesized by an ultrasonic exfoliation method using dimethylformamide as a dispersing agent. The composite shows high photocatalytic efficiency for hydrogen evolution.